The Effect of Corporate Culture and Employee Commitment and Transformational Leadership on Employee Performance at PT. Swabina Gatra (Cement Indonesia Group) - Putra, Zendy Dwi (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: Knowing and analyzing the effect of Corporate Culture on Employee Performance, Employee Commitment on Employee Performance, and Transformational Leadership on Employee Performance, data collection techniques using questionnaire filling with quantitative methodology distributed to a sample population of 110 people and processed using the Amos version 26 application and for the results of the study indicate that there is a significant effect of Corporate Culture on Employee Performance, as well as Employee Commitment on Employee Performance, and also Transformational Leadership on Employee Performance. Design/ Methodology/ Apporach: Quantitative Approach Findings: aspects that affect employee performance Research limitations/ implications: Implementation during working hours and in-house repairs Practical Implications: Culture, commitment, and transformational leadership affect employee performance Originality/ value: there is an influence on employee performance from the variables used Paper Type: Research Paper